DAMPAK PENYALURAN PEMBIAYAAN ARRUM PEGADAIAN SYARIAH KECAMATAN LOWOKWARU TERHADAP USAHA KECIL MENENGAH - Pamungkas, Yoga Satriya (Program Studi Ekonomi Pembangunan, 2023)
This research aims to determine the development of income and asset development of small businesses and to find out whether there are differences in income and assets in small businesses after obtaining Arrum financing from sharia pawnshops in Lowokwaru District. The data used in this research is primary data originating from distributing questionnaires with a sample of 87 respondents. The data analysis technique used is descriptive analysis, by collecting data and explaining the data obtained from distributing questionnaires and using a difference test to measure the significance of differences between two groups of paired data on an ordinal or interval scale. The research results show that each respondent who has carried out Arrum financing at a sharia pawnshop can increase the income they receive. Apart from that, the asset side also experienced an increase as a result of increased income. This is also reinforced by the results of different tests which show differences in income and assets before and after financing the Sharia Pegadaian Arrum in Lowokwaru District.